2020
DOI: 10.1111/issr.12236
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between different social expenditure schemes and poverty, inequality and economic growth

Abstract: In this article, we study how social expenditure is related to poverty, income inequality and GDP growth. Our main contribution is to disentangle these relationships by the following social expenditure schemes: 1) “old age and survivors”, 2) “incapacity”, 3) “health”, 4) “family”, 5) “unemployment and active labour market policies” and 6) “housing and others”. For this purpose, we employ OLS and 2SLS regression models using a panel data set for 22 Member States of the European Union from 1990 until 2015. We fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 58 publications
6
23
0
1
Order By: Relevance
“…However, our evidence also suggests that the economic outcomes of globalisation might vary across welfare regime since the intensity of the impact (and in some cases the sign) is regime dependent and previous literature as shown that e.g. economic growth and economic recovery respond differently to each component of social expenditure, Cammeraat ( 2020 ); Crociata et al ( 2020 ); Schuknecht and Zemanek ( 2021 ); Afonso and Jalles ( 2014 ); Furceri and Zdzienicka ( 2012 ). The previous findings indicate also that the economic and social dimensions of globalisation shape the levels of social expenditure across regimes, although economic globalisation is often identified in the public discourse as the main cause of welfare state retrenchment.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…However, our evidence also suggests that the economic outcomes of globalisation might vary across welfare regime since the intensity of the impact (and in some cases the sign) is regime dependent and previous literature as shown that e.g. economic growth and economic recovery respond differently to each component of social expenditure, Cammeraat ( 2020 ); Crociata et al ( 2020 ); Schuknecht and Zemanek ( 2021 ); Afonso and Jalles ( 2014 ); Furceri and Zdzienicka ( 2012 ). The previous findings indicate also that the economic and social dimensions of globalisation shape the levels of social expenditure across regimes, although economic globalisation is often identified in the public discourse as the main cause of welfare state retrenchment.…”
Section: Resultssupporting
confidence: 52%
“…From the perspective of the economic outcomes of globalisation (e.g. economic recovery and growth) it is also more informative to look at the composition of social expenditure as different social policies may have variegated economic outcomes, Cammeraat ( 2020 ); Crociata et al ( 2020 ); Furceri and Zdzienicka ( 2012 ). Kim and Zurlo ( 2009 ) is the single study from the ones reviewed in Table 2 that deals with this issue and only for a limited number of social expenditure categories: active and passive labour market spending and social service spending.…”
Section: Welfare State Regimes and The Social Spending Impacts Of Globalisation: Classification And Literature Overviewmentioning
confidence: 99%
“…Fonksiyonel sınıflandırma için VAR analizi etki tepki sonuçları, savunma ve sosyal güvenlik harcamaları ile ekonomik büyüme arasında negatif ilişkinin olduğu şeklindedir. Cammeraat (2020Cammeraat ( ), 1990Cammeraat ( -2015 dönemi için sosyal güvenlik harcamaları, eşitsizlik, yoksulluk ve ekonomik büyüme ilişkisini çalışmıştır. Regresyon analizinin kullanıldığı çalışmada; sosyal harcamaların yoksulluk ve eşitsizlikle negatif ilişkili olduğunu, ancak GSYH ile ilişkili olmadığı sonucuna ulaşmıştır.…”
Section: Literatür İncelemesiunclassified
“…In addition, it is found that trade openness, education expenditures, elderly population, participation in education decrease income inequality. Cammeraat (2020) studies that the effect direction of social spendings on poverty, income inequality and GDP growth in 22 Member States of the European Union from 1990 to 2015 by using panel data analysis by OLS and TSLS regressions. The findings show that social spendings negatively affect poverty and income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%